Expeditious Calculations of Electric Power Losses in 0.38–10 kV Electric Networks of Belarusian United Energy Systems - M. I. Fursanov; V. V. Makarevich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
An algorithmized methodology for expeditious calculations of technical losses in 0.38–10 kV electric networks of the Belarusian United Energy Systems has been developed on the basis of performance information which is formed by modern intellectual devices for registration and accumulation of data. The methodology allows to increase the accuracy in calculation of losses using more exact distribution of loadings between consumers of transformer substations and analyze an incremental value of  losses due to their asymmetrical connection of consumers and circuit asymmetry.